Online Customer Review dan Rating pada Keputusan Pembelian Aplikasi Shopee - Mawardani, Cita Agustin; Syarif, Muhammad (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
This research aims to provide empirical evidence of the the effect of online customer reviews and ratings on purchase decisions through the Shopee application in The Pabean Cantian Village of Surabaya. This study uses a quantitative approach. The population used in this research is among residents of Pabean Cantian Surabaya who use the Shopee application with a total of 70 observation samples taken using non-probability techniques. The data collection technique used a questionnaire and analyzed using the SPSS 29 tool. The research results showed that: a) partially, online customer reviews had a significant effect on purchasing decisions via the Shopee application among residents of Pabean Cantian Surabaya, b) partially, online customer ratings did not influence purchasing decisions via the Shopee application among residents of Pabean Cantian Surabaya, c) Simultaneously, online customer reviews and ratings influence purchasing decisions via the Shopee application among residents of Pabean Cantian Surabaya